Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Pelanggan di Toko Dasten Cell di Kecamatan Tallunglipu Kabupaten Toraja Utara - Ferdianto Kaluttu; Abedneigo Carter Rambulangi; Helba Rundupadang (CV. Ulil Albab Corp, 2024)
Every businessman needs to pay attention to appropriate marketing methods and strategies in managing their company to ensure stability in the face of competition. One of the shops that still stable are Toko Dasten Cell. The purpose of the research is to ascertain how customer satisfaction is impacted by service quality and cost. at Toko Dasten Cell. The research method is quantitative research. The informants were Toko Dasten Cell Customers. The results indicate that service quality (X1) has a positive influence on customer satisfaction (Y). This can be proven from the partial t test, namely the results of testing the customer satisfaction variable show tcount (4.743) > ttable (2.018). Price (X2) has a positive influence on customer satisfaction (Y). This can be seen from the partial price test showing tcount (3,481) > ttable (2,018)). The findings of this research, the most significant influence is the price variable where the coefficient of determination test result (R square) is 0.885 or 88.5%.